Let's talk, shall we? - oral skills in the teaching of English in Portugal - Cláudia Susana Martins; Maria Nazaré Cardoso (Escola Superior de Educação de Paula Frassinetti, 2015)
The present work aims at synthetising the different methodological approaches throughout the centuries and reflecting upon the evolution of the role of oral skills in the learning of foreign languages. These considerations create the opportunity to analyse the presence of these skills in the context of the teaching of English in Portugal. In view of this, we gathered the references to oral skills provided in the English Syllabi, which were published by the Ministry of Education (later the Ministry of Education and Science) in the 1990s. In addition to these, the formal evaluation of oral skills was made compulsory and enshrined in the Portuguese law in 2007. In characterising the Portuguese context, it was also imperative to examine the Curricular Targets and the Support Books for English in the 1st, 2nd and 3rd cycles of Basic Education (published between 2013 and 2015), in order to highlight the paradigmatic change that occurred with these last innovations introduced to oral skills and its current weight in pupils' evaluation. At last, we proceeded to ascertain the relevance of the external evaluation of English by means of the partnership established with the University of Cambridge and the tests "Key for Schools" (in 2014) and PET (in 2015) done at the end of the 9th year. In this analysis, it is important to consider the implementation of this process, as well as the results of these tests, so as to determine the degree of development of our pupils' linguistic proficiency.